2007
DOI: 10.1111/j.1095-8649.2007.01363.x
|View full text |Cite
|
Sign up to set email alerts
|

The timing and extent of ‘juvenile ovary’ phase are highly variable during zebrafish testis differentiation

Abstract: Gonad differentiation in male zebrafish involves a transformation from a ‘juvenile ovary’ to testis. In our study, this phenomenon was analysed using a stable transgenic line (vas::egfp) created by Krovel & Olsen (Mechanisms of Development, 116: 141–150, 2002). Our data obtained by histological and immunohistochemical methods show that the onset of enhanced green fluorescent protein (EGFP) expression marks the conversion of the bipotential gonad into a ‘juvenile ovary’, and its subsequent decrease in the males… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

11
151
1
4

Year Published

2007
2007
2022
2022

Publication Types

Select...
3
3

Relationship

1
5

Authors

Journals

citations
Cited by 142 publications
(167 citation statements)
references
References 33 publications
11
151
1
4
Order By: Relevance
“…5B). The former were shown earlier to develop normal (i.e., nontransforming) ovaries, whereas the latter were undergoing "ovary-to-testis" transformation (Wang et al, 2007). In the "normal" ovaries with increasing EGFP fluorescence cyp19a1a was expressed in the somatic cells (presumptive granulosa cells) surrounding the healthy oocytes (Fig.…”
Section: Showed Sexually Dimorphic Expression In the Zebrafish Gonadsmentioning
confidence: 99%
See 2 more Smart Citations
“…5B). The former were shown earlier to develop normal (i.e., nontransforming) ovaries, whereas the latter were undergoing "ovary-to-testis" transformation (Wang et al, 2007). In the "normal" ovaries with increasing EGFP fluorescence cyp19a1a was expressed in the somatic cells (presumptive granulosa cells) surrounding the healthy oocytes (Fig.…”
Section: Showed Sexually Dimorphic Expression In the Zebrafish Gonadsmentioning
confidence: 99%
“…During gonadal differentiation of zebrafish, males temporarily develop a "juvenile ovary" that is later degenerated and transformed into a testis (Takahashi, 1977;Maack and Segner, 2003;Wang et al, 2007). Although histological analysis showed the presence of degenerating oocytes in these transforming gonads and apoptosis was implicated to be involved with the process (Uchida et al, 2002), the molecular mechanism of this "juvenile ovary-totestis" transformation has never been addressed.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Sexing of the juvenile zebrafish by examining external phenotypes at this age is not possible. Therefore, we included in the hierarchical clustering samples from the Tg(vasa:vasa-egfp) transgenic line (47) collected at similar age (35 and 42 dpf), because it allows for early sexing from 16 dpf onward (25). This way, we were able to infer the sex of the two juvenile groups at control temperature (JCT1 and JCT2).…”
Section: Expression Analysis Of Selected Genes Confirmed the Existencmentioning
confidence: 99%
“…Then, during the 21-to 35-dpf period, in the future males the juvenile ovaries undergo apoptosis and are transformed into testes, with interindividual variation in the timing and duration to complete this process. In contrast, ovarian differentiation continues in the future females (25), with an increase in cytoplasm volume of oocytes at around 60 dpf. Transcriptomic analysis of zebrafish sex differentiation has shown that apoptosis (24), activated by the p53 signaling pathway (26), is required for testis differentiation, whereas up-regulation of the canonical Wnt and NF-κB signaling pathways is needed for ovarian differentiation (27,28).…”
mentioning
confidence: 99%